2022
DOI: 10.1163/22105832-bja10022
|View full text |Cite
|
Sign up to set email alerts
|

Divergence and contact in Southern Bantu language and population history

Abstract: In this paper we present a new, lexicon-based phylogeny of 34 Southern Bantu languages, and combine it with previous insights from linguistics, archaeology, and genetics to study the history of Southern Bantu languages and their speakers. Our phylogeny shows all Southern Bantu languages to derive from a single, direct ancestor, which contrasts with archaeological evidence indicating separate migrations of Bantu speakers into southern Africa. This suggests that the Bantu languages spoken by the first migrants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…Kgalagadi (S311) is part of the Sotho-Tswana cluster, together with Tswana, Northern and Southern Sotho, among others. A recent lexicon-based phylogenetic classification of Southern Bantu languages confirmed the unity of the Sotho-Tswana cluster, and classified Kgalagadi within Sotho-Tswana as a sister clade to Southern Sotho, Lozi, Tswana and Tawana (Gunnink, Chousou-Polydouri & Bostoen 2023). Furthermore, it classified the Ngologa variety of Kgalagadi, as described by Lukusa & Monaka (2008), and Tjhauba as direct sister branches, confirming the close relationship between these two varieties.…”
Section: The Tjhauba Variety Of Kgalagadisupporting
confidence: 57%
“…Kgalagadi (S311) is part of the Sotho-Tswana cluster, together with Tswana, Northern and Southern Sotho, among others. A recent lexicon-based phylogenetic classification of Southern Bantu languages confirmed the unity of the Sotho-Tswana cluster, and classified Kgalagadi within Sotho-Tswana as a sister clade to Southern Sotho, Lozi, Tswana and Tawana (Gunnink, Chousou-Polydouri & Bostoen 2023). Furthermore, it classified the Ngologa variety of Kgalagadi, as described by Lukusa & Monaka (2008), and Tjhauba as direct sister branches, confirming the close relationship between these two varieties.…”
Section: The Tjhauba Variety Of Kgalagadisupporting
confidence: 57%
“…Despite consensus on its demic nature, genetic studies of the BSP expansion have not revealed the typical serial-founder effect observed when small migrant groups settle in new areas, leading to a decrease in genetic diversity with increasing distance from the putative homeland 13 , 26 , 27 . This might be a result of subsequent genetic diversity increases from admixture with local populations or long-distance interactions with later Bantu-speaking migrations, known as ‘spread-over-spread’ events 2 , 20 , 28 , 29 . This underlying complexity, coupled with the different migration histories proposed by linguistics, archaeology and genetics, makes the expansion of BSP interesting for exploration with newer population genetic methods and modelling approaches that are spatiotemporally sensitive.…”
Section: Mainmentioning
confidence: 99%
“…Despite agreement on its demic nature, previous genetic studies on the expansion of BSP did not find the typical serial founder effect expected when small migrant groups settle in new areas, leading to a decrease in genetic diversity with increasing distance from the putative homeland 22,23 . The signal of founder events could have been erased by a subsequent increase of genetic variation through admixture with local populations and/or via long-distance contacts involving later migrations of Bantu speaking communities, so-called spread-over-spread events 4,16,24,25 . This underlying complexity, coupled with the different migration routes and patterns proposed by linguistics, archeology and genetics, makes the expansion of BSP interesting for exploration with newer population-genetic methods and modeling approaches that are spatio-temporally sensitive.…”
Section: Mainmentioning
confidence: 99%
“…It has been suggested that the initial expansion of BSP across sub-equatorial Africa was followed by subsequent migrations of BSP following similar routes, creating a pattern of spread-over-spread events 43 , which in some cases may have replaced earlier settlers and their languages 16,25,44 . Due to shifts to newcomers' languages and the subsequent or independent death of first settlers' languages, certain branches of the Bantu language family tree possibly no longer represent the initial expansion of BSP 45 .…”
Section: Spread-over-spread Events Versus Genetic Continuitymentioning
confidence: 99%